Effect of the root-lesion nematode (Pratylenchus penetrans) on annual bluegrass (Poa annua) - Bélair, Guy; Simard, Louis (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2008)
This study was undertaken to assess the effect of various population densities of the root-lesion nematode (Pratylenchus penetrans) on the growth of annual bluegrass (Poa annua) under controlled conditions. In two separate experiments, the nematodes were inoculated at concentrations of 100, 500, 1000 or 5000 nematodes 100 cm‑3 soil per pot or per tube. Nine wk post-inoculation, root P. penetrans populations had increased linearly with initial nematode concentrations in both experiments. Growth and quality of turfgrass were uniform for all treatments, with no significant difference from the control. Under the current experimental conditions, P. annua was shown to be a tolerant host plant to P. penetrans.